Cytotoxicity and antimicrobial test of the bioactive compound isolated from Stylissa flabelliformis sponge - Erna Prawita Setyowati; Sudarsono .; Subagus Wahyuono (Indonesian Journal of Pharmacy, 2004)
A research of cytotoxicity and antimicrobial test of bioactive compound of Stylissa flabelliformis sponge have been done. Cytotoxicity test were conducted on myeloma cells, while antimicrobial test were conducted against Staphylococus aureus,Eschericia coli and Candida albican. The research was initiated with the isolation of bioactive compound from the active fraction of sponge S. Stylissa monitored by Brine shrimp Lethality tes (BST). The active fraction was chromatograped with silica gel as its immobile phase and the mixture of hexane and ethyl acetate (1:1 ) as the mobile phase to obtain compound 1,2,3 and 4.Compound 3 has the most toxic character because it could kill A. salina equal to 100% at dose 25 mg/ml, and has LC50 of 0,9 mg/ml. Cytotoxicity test with direct staining method using tripan blue on myeloma cell at density of 4,5x10 cell / 100.ul showed that the compound 3 had a high activity against myeloma cell, having LC50 equal to 0,08 mg/ml.The result of antimicrobial effect showed that compound 3 was a fungicide against Candida albicans but having no activity on Staphylococcus aureus and Eschericia coliKey words: sponge, Stylissa flabelliformis , cytotoxicity, fungicide